Financial Toxicity Intervention Improves Outcomes in Patients With Hematologic Malignancy. Issue 9 (16th September 2022) - Knight, Thomas G.; Aguiar, Melissa; Robinson, Myra; Morse, Allison; Chen, Tommy; Bose, Rupali; Ai, Jing; Ragon, Brittany K.; Chojecki, Aleksander L.; Shah, Nilay A.; Sanikommu, Srinivasa R.; Symanowski, James; et al.
Abstract : PURPOSE: Patients with hematologic malignancies are extremely vulnerable to financial toxicity (FT) because of the high costs of treatment and health care utilization. This pilot study identified patients at high risk because of FT and attempted to improve clinical outcomes with comprehensive intervention. METHODS: All patients who presented to the Levine Cancer Institute's Leukemia Clinic between May 26, 2019, and March 10, 2020, were screened for inclusion by standardized two question previsit survey. Patients screening positive were enrolled in the comprehensive intervention that used nurse navigators, clinical pharmacists, and community pro bono financial planners. Primary outcomes were defined as improvement in mental and physical quality of life in all patients and improvement in overall survival in the high-risk disease group. RESULTS: One hundred seven patients completed comprehensive intervention. Patients experiencing FT had increased rates of noncompliance including to prescription (16.8%) and over-the-counter medications (15.9%). The intervention resulted in statistically significantly higher quality of life when measured by using Patient-Reported Outcomes Measurement Information System physical (12.5 ± 2.2 v 13.7 ± 1.8) and mental health scores (11.4 ± 2.2 v 12.4 ± 2.2; all P < .001). In patients with high-risk disease (as determined by using disease-specific scoring systems), risk of death in those receiving the intervention was 0.44 times the risk of death in those without the intervention after adjusting for race, and treatment with stem-cell transplant, oral chemotherapy, or immunotherapy (95% CI, 0.21 to 0.94; P = .034). CONCLUSION: Screening and intervention on FT for patients with hematologic malignancies is associated with increased quality of life and survival.